2003
DOI: 10.1176/appi.ajp.160.11.1938
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Emotional Self: An fMRI Study Using Positive and Negative Emotional Words

Abstract: A widely distributed network of brain areas contributes to emotional processing. Among these regions, the right dorsomedial prefrontal cortex is one main area mediating self-reference. By providing a personal perspective in the evaluation of emotional stimuli, the right dorsomedial prefrontal cortex may mediate cognitive processes, such as those involved in psychotherapy, that guide self-regulation of emotional experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
340
4
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 554 publications
(382 citation statements)
references
References 32 publications
31
340
4
7
Order By: Relevance
“…The cognitive component of the task (that is 'like me/not like me') engaged the MPFC irrespective of the valence of the trait word, whereas the affective component of the task (that is 'favourable/unfavourable') was resolved in ventral anterior cingulate cortex. 10 Taken together, 7,8,10 the above findings implicate medial frontal, cingulate, parietal cortex and precuneus in tasks that require self-referential processing of personality-trait words.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…The cognitive component of the task (that is 'like me/not like me') engaged the MPFC irrespective of the valence of the trait word, whereas the affective component of the task (that is 'favourable/unfavourable') was resolved in ventral anterior cingulate cortex. 10 Taken together, 7,8,10 the above findings implicate medial frontal, cingulate, parietal cortex and precuneus in tasks that require self-referential processing of personality-trait words.…”
Section: Introductionmentioning
confidence: 81%
“…In a whole brain analysis, significant activations were identified using cluster-based thresholding of statistical images with a height threshold of Z > 2.3 and a (corrected) spatial extent threshold of P < 0.05. 33 Given the findings from earlier neuroimaging studies implicating the right MPFC and vACC, 7,8,10 regions of interest (right MPFC, 8 mm sphere; and vACC, 12 mm sphere) were generated based on the coordinates described by Moran et al 10 Approximate Brodmann's Areas (BA) were identified by transformation of MNI coordinates into Talairach space. 34 (Additional information available at http://www.mrc-cbu.cam.ac.uk/ Imaging.)…”
Section: Visual Stimulation Paradigmmentioning
confidence: 99%
See 2 more Smart Citations
“…Converging evidence within the functional neuroimaging literature indicates that cortical midline structures (CMS) play an essential role in such self‐referential processing (Northoff & Panksepp, 2008; Northoff et al., 2006; Panksepp & Northoff, 2009). Several functional magnetic resonance imaging (fMRI) studies found that the medial prefrontal cortex (mPFC) and, specifically, the ventromedial prefrontal cortex (vmPFC) are involved in self‐referential processing, particularly if the content is emotional (Araujo, Kaplan, Damasio, & Damasio, 2015; D'Argembeau et al., 2011; Fossati et al., 2003; Kim & Johnson, 2015; van der Meer, Costafreda, Aleman, & David, 2010). Interestingly, previous fMRI studies indicate that the mPFC is also involved in emotion regulation and extinction learning (Garvert, Moutoussis, Kurth‐Nelson, Behrens, & Dolan, 2015; Ochsner, Silvers, & Buhle, 2012; Peters, Kalivas, & Quirk, 2009), two processes that are found to be dysfunctional in psychopathological states with disrupted self‐referential processing like depression or anxiety disorders (Hofmann et al., 2013).…”
Section: Introductionmentioning
confidence: 99%